2016
DOI: 10.5194/amt-9-535-2016
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sensor analysis of convective activity in central Italy during the HyMeX SOP 1.1

Abstract: Abstract.A multi-sensor analysis of convective precipitation events that occurred in central Italy in autumn 2012 during the HyMeX (Hydrological cycle in the Mediterranean experiment) Special Observation Period (SOP) 1.1 is presented. Various microphysical properties of liquid and solid hydrometeors are examined to assess their relationship with lightning activity. The instrumentation used consisted of a C-band dual-polarization weather radar, a 2-D video disdrometer, and the LINET lightning network. Results o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…The increased presence of the vertically aligned ice could be explained by the reported atmospheric lightning, although a straightforward relation cannot be assumed (Hubbert et al, 2014;Roberto et al, 2016). In terms of vertical ice detection, a comparison with the conventional (fuzzy logic) approach (Fig.…”
Section: Detection Performancementioning
confidence: 99%
“…The increased presence of the vertically aligned ice could be explained by the reported atmospheric lightning, although a straightforward relation cannot be assumed (Hubbert et al, 2014;Roberto et al, 2016). In terms of vertical ice detection, a comparison with the conventional (fuzzy logic) approach (Fig.…”
Section: Detection Performancementioning
confidence: 99%
“…for temperatures colder than −5 • C), and found that these relationships are relatively invariant between different climate conditions. Roberto et al (2016) found a marked relationship between cloud graupel content by using C-band radar.…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly based on [17] and is tailored to identify meteorological targets, with a particular emphasis on the hydrometeors involved in convective events. Recent updates are described in [9,27], for X-band and C-band, respectively, that show the membership functions used. Such functions are not so different from those reported in the literature and therefore the results obtained should not be significantly influenced by the choice of FL classifier.…”
Section: Support Vector Machine Implementation Of Hcamentioning
confidence: 99%
“…Typically, HCAs classify hydrometeors by analyzing the set of dual-polarization measurements pertinent to a single radar measurement volume. Most of the recent literature on fuzzy logic HCA aimed at improving the membership functions (e.g., [7]) also focusing on specific classes [8,9]. Steps forward to improve the robustness of the fuzzy logic approach are the semi-supervised approach in [10], which improved the spatial coherency of classification maps by exploiting measurements in the neighboring bins, and the unsupervised clustering approach [11] to define the number of classes and the membership functions.…”
Section: Introductionmentioning
confidence: 99%